Analytical design of compact multiband bandpass filters with multiconductor transmission lines and shunt open stubs - Pérez-Escribano, Mario; Márquez-Segura, Enrique; Sánchez-Martínez, Juan José (MDPI, 2023)
A compact topology for implementing compact multiband bandpass filters is presented in this paper. To achieve the desired frequency response, two identical short-circuited multiconductor transmission lines (MTLs) and properly connected shunt open stubs are interconnected. Using this configuration, it is possible to design multiband bandpass filters effortlessly. As both the MTLs and the stubs are distributed elements, spur-line band-stop filters are added to mitigate the first replica of the structure’s frequency response. To assess the behavior of the developed filter design procedure, a prototype consisting of a six fingers-MTL and two shunt open stubs has been designed, manufactured, and analyzed, showing excellent agreement between analytical and measured results, considering that no simulation or optimization process has been performed during the design process, just for result verification. Furthermore, it is possible to establish a design criterion that allows the fast and reliable synthesis of multiband responses by varying just a small number of geometrical parameters of the MTLs and the corresponding stubs.
Keywords: Filtros de paso de banda - Diseño; Líneas de transmisión; Telecomunicaciones; Banda de conducción; Filter design; Multiband bandpass filter; Multiconductor transmission lines